Metabolic and Renal Adverse Effects of Antiretroviral Therapy in HIV-infected Children and Adolescents. Issue 5 (May 2015) - Fortuny, Clàudia; Deyà-Martínez, Ángela; Chiappini, Elena; Galli, Luisa; de Martino, Maurizio; Noguera-Julian, Antoni
Abstract : Worldwide, the benefits of combined antiretroviral (ARV) therapy in morbidity and mortality due to perinatally acquired human immunodeficiency virus infection are beyond question and outweigh the toxicity these drugs have been associated with in HIV-infected children and adolescents to date. In puberty, abnormal body fat distribution is stigmatizating and leads to low adherence to ARV treatment. The other metabolic comorbidities (mitochondrial toxicity, dyslipidemias, insulin resistance and low bone mineral density) and renal toxicity, albeit nonsymptomatic in most children, are increasingly being reported and potentially put this population at risk for early cardiovascular or cerebrovascular atherosclerotic disease, diabetes, pathologic fractures or premature renal failure in the third and fourth decades of life. Evidence from available studies is limited because of methodological limitations and also because of several HIV-unrelated factors influencing, to some degree, the development of these conditions. Current recommendations for the prevention, diagnosis, monitoring and treatment of metabolic and renal adverse effects in HIV-children and adolescents are based on adult studies, observational pediatric studies and experts' consensus. Healthy lifestyle habits (regarding diet, exercise and refraining from toxic substances) and wise use of ARV options are the only preventive tools for the majority of patients. Should abnormal findings arise, switches in one or more ARV drugs have proved useful. Specific therapies are also available for some of these comorbidities, although the experience in the pediatric age is still very scarce. We aim to summarize the epidemiological, clinical and therapeutic aspects of metabolic and renal adverse effects in vertically HIV-infected children and adolescents.